Health workforce perceptions on telehealth augmentation opportunities - L. T. Thomas; C. M. Y. Lee; K. McClelland; G. Nunis; S. Robinson; R. Norman (BMC, 2023)
Abstract Background The availability and use of telehealth to support health care access from a distance has expanded in response to the COVID-19 pandemic. Telehealth services have supported regional and remote health care access for many years and could be augmented to improve health care accessibility, acceptability and overall experiences for both consumers and clinicians. This study aimed to explore health workforce representatives' needs and expectations to move beyond existing telehealth models and plan for the future of virtual care. Methods To inform recommendations for augmentation, semi-structured focus group discussions were held (November-December 2021). Health workforce representatives with experience in health care delivery via telehealth across country Western Australia were approached and invited to join a discussion. Results Focus group participants included 53 health workforce representatives, with between two and eight participants per discussion. In total, 12 focus groups were conducted: seven were specific to regions, three with staff in centralised roles, and two with a mixture of participants from regional and central roles. Findings identified four key areas for telehealth augmentation: improvements required to existing service practice and processes; equity and access considerations; health workforce-focussed opportunities; and consumer-focussed opportunities. Conclusions Following the onset of the COVID-19 pandemic and the rapid increase in health services delivered via telehealth modalities, it is timely to explore opportunities to augment pre-existing models of care. Workforce representatives consulted in this study suggested modifications to existing process and practice that would improve the current models of care, and recommendations on ways to improve clinician and consumer experiences with telehealth. Improving experiences with virtual delivery of health care is likely to support continued use and acceptance of this modality in health care delivery.